2010
DOI: 10.1002/pola.23874
|View full text |Cite
|
Sign up to set email alerts
|

Density functional study for the polymerization of ethylene monomer using a new nickel catalyst

Abstract: The present computational study was designed to study the polymerization of ethylene catalyzed by a new Nibased PymNox organometallic compound. Recently, we have synthesized and tested the behavior of this type of catalyst in olefin polymerization. It has been experimentally observed that the unsubstituted catalyst Ni2 (aldimino PymNox catalyst) is less active than the methyl substituted Ni1 (acetaldimino PymNox catalyst) analogue. The reactivity of both catalysts was examined using density functional theory (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Termination: In a similar way to that observed in the quantum chemical calculations on the square-planar ethylene alkyl complexes (7 a and 7 b, Scheme 4), [70,[84][85][86][87][88][89] the phosphine alkyl complexes (1 a and 1 b, Scheme 4) display preferences with respect to cis/trans isomerization. Higher energies were obtained for isomers with the propyl trans to the more strongly donating and more sterically hindered phosphorus (for I) or nitrogen (for II and III), that is, the relative energies of these isomers were found to be 1 a < 1 b.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Termination: In a similar way to that observed in the quantum chemical calculations on the square-planar ethylene alkyl complexes (7 a and 7 b, Scheme 4), [70,[84][85][86][87][88][89] the phosphine alkyl complexes (1 a and 1 b, Scheme 4) display preferences with respect to cis/trans isomerization. Higher energies were obtained for isomers with the propyl trans to the more strongly donating and more sterically hindered phosphorus (for I) or nitrogen (for II and III), that is, the relative energies of these isomers were found to be 1 a < 1 b.…”
Section: Resultssupporting
confidence: 69%
“…Propagation: A number of computational investigations have concluded that, in the case of (k 2 -P,O) or (k 2 -N,O) asymmetric bidentate ligands with d 8 square-planar geometries, the energetically most favorable ethylene insertion transition state involves the alkyl chain trans to the more sterically hindered and strongly donating phosphorus or nitrogen of the bidentate ligand, that is, 7 b_TS in Scheme 4. [70,[84][85][86][87][88][89] The energetically most favorable ethylene p complexes, on the other hand, most commonly have the alkyl chain situated cis to the more sterically hindered and strongly donating phosphorus or nitrogen of the bidentate ligand, as in complex 7 a in Scheme 4. For catalysts II and III, however, the relative stabilities of the two isomers are typically very similar (within 1.0 kcal mol À1 ), [70,84,85] consistent with our free-energy differences of 0.8 and À0.1 kcal mol À1 for isomers 7 a and 7 b, respectively (see Table 2).…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…The MD method is a deterministic technique that simulates the motion of a system under the influence of a given potential [FF, as that shown in Equation 16] by following molecular conformations according to Newton's equation of motion. The system of equations of motion of N particles is: (17) The time evolution of the particles (trajectory) is obtained by integrating the equations of motion [Equation (17)] over discrete steps in time (time-step, ∆t) using a finite difference method. The time-step must be sufficiently small to avoid discrete integration errors.…”
Section: Molecular Dynamics (Md)mentioning
confidence: 99%
“…With regards to polymer physics, PE is undoubtedly the most studied polymer. The reasons for this are its chemical simplicity, its high level of production in the last 50 years and the availability of model materials obtained by different synthetic routes (long chain paraffins [2], single-site catalyst PE that include modelling reactions [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] and hydrogenated polybutadienes [22][23][24]. In addition, architecture is generally well characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have also theoretically addressed catalyst behavior during polymerization. Our group has actively contributed to this field with a number of computational studies. For this type of study, density functional theory (DFT) has allowed the treatment of polymerization catalyst systems using the computational resources available at the time over the past 20 years.…”
Section: Introductionmentioning
confidence: 99%